Nutrient digestibility of wheat wet and dried distillers' grain in growing pigs - Gautam, Kishor Kumar (2011)
The research was conducted to evaluate ileal and total tract digestibility of crude protein (CP), organic matter (OM) and energy in growing pigs supplied with dietary inclusion of commercially available wheat wet distillers grain with solubles (WWDGS) and wheat dried distillers’ grain with solubles (WDDGS). Seven castrated male pigs with post valve t-caecum (PVTC) cannulas with an average initial body weight of 79 kg were fed two experimental diets (W and D) in a change-over design. Diet W was composed of 50% WWDGS and 50% basal diet, and diet D was composed of 50% WDDGS and 50% basal diet. The basal diet was composed of corn starch, sugar, premix and titanium dioxide. A casein-based diet was fed prior to and after the study to estimate the basal endogenous nitrogen and amino acid (AA) losses. Apparent ileal digestibility (AID) for CP in diet W was higher (p<0.05) than for diet D, whereas the AID for energy and OM remained similar (p>0.05) between the diets. Apparent total tract digestibility (ATTD) was recorded higher (p<0.0001) for CP in diet W than in diet D. In addition, higher ATTD was recorded for OM in diet W with no significant difference (p>0.05) in energy digestibility. Endogenous losses for each pig was evaluated separately and used for calculation of standardized ileal digestibility (SID) of CP and AA. The average endogenous losses of CP were from the pre- and post period was 8.53±0.95 g/kg DM of digesta. The SID value for CP, methionine and lysine in diet W was higher (p<0.05) than for diet D. There was significant increased variation in lysine digestibility in WWDGS than in WDDGS. Differences between the production plants and in chemical composition between grain sources were the main reasons for different nutritional values between the distillers grain products. Despite excellent nutritional properties, the low dry matter content, decreased P digestibility and high transportation cost, limits the use of WWDGS to a local area within reasonable distance from the factory.